Molecular docking study of aptamer-based biosensor for detection of Shiga Toxin (Stx) protein from Escherichia coli O157:H7 - Mohamad Azmi, Muhammad Fakhrullah; Wan Ayub, Wan Mardhiyana; Ibrahim, Izzah Afifah; Redzuan, Muhammad Fadzlisyam; Ismadi, Irfan Danial; Mohd Ghazali, Mohd Ifwat; Mohamad Jamali, Muhamad Arif; Azmi, Liyana; Zainal, Nur Zaireena; Abdul Hamid, Nazefah; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The increasing prevalence of pathogenic Escherichia coli (E. coli) in water and food sources poses a significant threat to public health, necessitating the development of rapid and accurate biosensor detection methods such as aptamer-based biosensors due to their high specificity and sensitivity. Aptamers are nucleic acids that can bind with high affinity and specificity to a range of target molecules. This research aims to investigate biophysical mechanisms by utilizing biophysics simulations such as molecular free energy calculation and molecular docking to elucidate the interaction between specific aptamer with E. coli protein such as Shiga Toxin (Stx). The methodology involves characterizing aptamer-E. coli interactions, identifying key aptamer structural features and docking analysis of binding process between aptamer and E. coli. In conclusion, this research bridges theory for future applications, providing a framework for developing advanced biosensing technologies, by using the in-silico strategies that allowed the detection of aptamer-target interaction during molecular docking processes.